Compression stockings and the prevention of symptomatic venous thromboembolism: data from the Tinzaparin in Acute Ischaemic Stroke Trial - Sprigg, Nikola; Gray, Laura J.; Bath, Philip M.W.; Boysen, Gudrun; de Deyn, Peter Paul; Leys, Didier; Lindenstrom, Ewa; O'Neill, Desmond; Ringelstein, Bernd; van der Sande, Jan Jacob (Elsevier, 2005)
Background: Venous thromboembolism (VTE) is a well recognised and preventable complication of acute stroke. While graduated compression stockings reduce the risk of VTE in surgical patients their benefit in acute stroke remains uncertain. Methods: The relationship between symptomatic VTE and use of stockings using observational data from the ‘Tinzaparin in Acute Ischaemic Stroke Trial’, which compared 10 days of treatment with tinzaparin (175 IU.kg-1 or 100 IU.kg-1) with, aspirin (300 mg od), was assessed using logistic regression adjusted for known VTE risk factors and treatment. Results: Symptomatic VTE occurred in 28 patients (1.9%, DVT 18, PE 13) within 15 days of enrolment in 1,479 patients. Patients wearing one or two stockings for any period of time during the first 10 days (n=803) had a non-significant increase (odds ratio, OR 2.45, 95% confidence interval, CI 0.95 - 6.32) in the risk of symptomatic VTE. In contrast, those wearing bilateral stockings for 10 days (n=374) had a non-significant reduction in the odds of symptomatic VTE as compared to those who wore no stockings or wore them for less than 10 days (OR 0.65, 95% CI 0.26-1.65). Mild stroke and treatment with tinzaparin were associated with a reduced risk of VTE. Conclusions: Bilateral graduated compression stockings may reduce the incidence of VTE by one-third in patients with acute ischaemic stroke. However, the uncertainty in this finding, low frequency of symptomatic VTE, potential for stockings to cause harm, and cost of stockings highlight the need for a large randomised-controlled trial to examine the safety and efficacy of stockings in acute stroke.